Influence of neurotropic and metabolic drugs on structural and functional state of lipid matrix of the cell membrane - Seba, M. V.; Khomenko, M. O.; Nosevych, D. K.; Golubev, M. I.; Kaplunenko, V. G.; Byelinska, I. V.; Rybalchenko, V. K. (НУБіП України, 2020)
Lately, more and more often to stimulate the reproductive function of animals people use biochemical products, which are based on neurotropic and metabolic compounds and trace elements of nanobiotechnological origin. In order to new biotechnical drugs search and development, and more effective and safe combinations of dietary supplements in them, one should know Biochemical mechanisms of membranotropic action of these substances on a cell. Since these substances can lead to physiological changes in the cell and trigger nonspecific toxic effects on the body of animals depending on dose and period of action. The article presents the results of studies on the effects of neurotropic and metabolic drugs on structural and functional state of lipid matrix of the cell membrane.
Вплив нейротропно-метаболічних препаратів на структурно-функціональний стан ліпідного матриксу клітинних мембран
Останім часом, все частіше для стимуляції репродуктивної функції тварин, застосовують біотехнологічні препарати, які створені на основі нейротропно-метаболічних сполук та мікроелементів нанобіотехнологічного походження. Для пошуку і розробки нових біотехнологічних препаратів та для більш ефективних і безпечних комбінацій в них біологічно активних речовин необхідно знати біохімічні механізми мембранотропної дії цих речовин на клітину. Оскільки ці речовини в залежності від дози та періоду дії можуть приводити до фізіологічних змін у клітині та ініціювати неспецифічні токсичні ефекти на організм тварин. У статті представлені результати досліджень впливу складових препаратів нейротропно-метаболічної дії на структурно-функціональний стан ліпідного матриксу клітинних мембран.
Keywords: Glutaminate; Succinate; nanovulin; Copper; membranes; citrate